Pregonero’s Word. Icaza as Reviser of Icaza: The Parenthesis as a Folding Operation and Space of Pleasure in Huasipungo - Gomezjurado Quezada, Guillermo (2022)
In this paper, a reading of the use of parenthesis in Huasipungo, from Jorge Icaza, is made, realizing that its number increase in the different versions of the book —the first version, from 1934, and the definitive version, from 1960, are here compared—. The proposal of this paper consists of thinking on the parenthesis as a folding operation. With this choice, “a style continuously cut by parenthesis that puts the brakes on the progress of the story” as was framed by Manuel Corrales, is no longer appreciated. On the other hand, the novel is seen as a tumultuous narrative that incorporates and wraps joyful elements to the story. Also, the parenthesis used by Icaza is identified as a resource for displaying sardonic phrases which are used for defining some of his characters.